2017
DOI: 10.1111/cars.12173
|View full text |Cite
|
Sign up to set email alerts
|

Balancing the Scales: Negotiating Father's Parental Leave Use

Abstract: Studying couples who shared parental leave presents the opportunity to explore decision-making processes that may challenge conventional care arrangement typical of early parenthood. Interviews with 33 Canadian heterosexual couples indicate gendered sticking points in the division of official leave time. Whether fathers took leave because of their personal desires or material circumstances, this study finds that men and women did not enter negotiations on a level playing field. Strong cultural support for moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 53 publications
(73 reference statements)
4
21
0
Order By: Relevance
“…This fact has also been identified in Spain by González and Jurado (2015). Consistent with other scholars (Beglaubter, 2017;Deutsch, 2007;Fernandez-Lozano, 2019;Holter, 2007), these authors found that active fathers conform to the following two different profiles: those who are involved as a result of a personal commitment to gender egalitarianism and those who are involved as a result of their circumstances (i.e., unemployment or a less-demanding job).…”
Section: The Spanish Parental Leave System and Its Usesupporting
confidence: 84%
See 1 more Smart Citation
“…This fact has also been identified in Spain by González and Jurado (2015). Consistent with other scholars (Beglaubter, 2017;Deutsch, 2007;Fernandez-Lozano, 2019;Holter, 2007), these authors found that active fathers conform to the following two different profiles: those who are involved as a result of a personal commitment to gender egalitarianism and those who are involved as a result of their circumstances (i.e., unemployment or a less-demanding job).…”
Section: The Spanish Parental Leave System and Its Usesupporting
confidence: 84%
“…Job conditions, such as working hours, flexibility, job stability, and income may facilitate or hinder parents’ use of unpaid parental leave. For example, the use of leave by other coworkers (Beglaubter, 2017; Lapuerta et al, 2011), an employer’s positive attitude (Bygren & Duvander, 2006; Crompton, 2006), working in a family-friendly environment (Escot et al, 2012) or larger companies (Zhelyazkova & Ritschard, 2018) and working in the public sector (Beglaubter, 2017; Escot et al, 2014; Lammi-Taskula, 2008) are factors positively related to parental leave use. However, organizational barriers affect men to a greater extent than women (Duvander, 2014).…”
Section: Labor-market Conditions and Gender-role Attitudes: Two Compementioning
confidence: 99%
“…Second, time diaries in the GSS only provide information about one respondent per household. As such, this study cannot speak to the household‐ and family‐level dynamics, such as negotiations between couples regarding leave‐taking (Beglaubter, ; McKay & Doucet, ) or the share of caregiving tasks and responsibilities. Future research could explore how mothers' involvement in caregiving is shifted by fathers' leave‐taking and early involvement in caregiving.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, reserved or "use it or lose it" leave policies result in higher uptake and longer leaves for fathers (Margolis et al, 2019;O'Brien, 2009). Reserved paternity leave, especially if it is generous, provides economic incentives that may help displace normative gender expectations with financial logic (Beglaubter, 2017;Gangl & Ziefle, 2015;McKay & Doucet, 2010). These policies can also help lessen stigma around leave-taking by giving fathers a publicly legitimated bargaining tool with employers (Harvey and Tremblay, 2018;McKay & Doucet, 2010).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation